The relationship between depression risk perception and self-help behaviours in high risk Canadians: a cross-sectional study - Emily Warner; Molly Nannarone; Rachel Smail-Crevier; Douglas Manuel; Bonnie Lashewicz; Scott Patten; Norbert Schmitz; Glenda MacQueen; Jian Li Wang (BMC, 2020)
Abstract Background Self-help may reduce the risk of depression, and risk perception of depression may influence initiating self-help. It is unknown how risk perception is associated with self-help behaviours. The objectives of this study are to (1) describe the self-help strategies used by high-risk Canadians in relation to the accuracy of perceived depression risk, by sex, and (2) identify demographic and clinical factors associated with self-help behaviours. Methods Baseline data from a randomized controlled trial including 358 men and 356 women at high-risk of developing depression were used. Following methods used in cancer research, risk perception accuracy was determined by comparing the participant's self-perceived and objective risk of developing depression and classifying as accurate, over-estimation and under-estimation based on a ± 10% threshold. The participant's objective depression risk was assessed using sex-specific multivariable risk predictive algorithms. Frequency of using 14 self-help strategies was assessed. One-way ANOVA testing was used to detect if differences in risk perception accuracy groups existed, stratified by sex. Linear regression was used to investigate the clinical and demographic factors associated with self-help behaviours, also stratified. Results Compared to accurate-estimators, male over-estimators were less likely to "leave the house daily," and "participate in activities they enjoy." Male under-estimators were also less likely to "participate in activities they enjoy." Both male 'inaccurate' perception groups were more likely to 'create lists of strategies which have worked for feelings of depression in the past and use them'. There were no significant differences between self-help behaviours and risk perception accuracy in women. Regression modeling showed negative relationships between self-rated health and self-help scores, irrespective of sex. In women, self-help score was positively associated with age and educational attainment, and negatively associated with perceived risk. In men, a positive relationship with unemployment was also seen. Conclusions Sex differences exist in the factors associated with self-help. Risk perception accuracy, work status, and self-rated health is associated with self-help behaviours in high-risk men. In women, factors related to self-help included age, education, self-rated health status, and perceived risk. More research is needed to replicate findings. Trial registration Prospectively registered at ClinicalTrials.gov ( NCT02943876 ) as of 10/21/16.